(untitled) (Fiep Bulletin - online, 2013)
Introduction: The strength training that focuses on increasing muscle power is done with quick and explosive efforts are interspersed series of repetitions of a particular exercise with rest intervals. The breadth of the recovery interval between sets affects the acute metabolic responses, the chronic responses of muscle strength, performance of subsequent sets, and hormonal responses. Objective: To investigate the influence of different rest intervals on performance of maximum repetitions between series of strength training. Methods: The sample comprised 12 young men (21-31 years old). Initially held an evaluation for anthropometric measurements of weight, height and BMI of the sample, then the subjects participated in the 1RM test for the evaluation of muscle strength. Tests of maximum repetition for determining intervals of two and four minutes were performed in a leg press machine 45º, which induces the creation of motion knee extension against a pressure plate, we used 90% of maximum identified in first day of testing. Results: The recovery interval didn’t influence the performance of maximum repetition in each series, however, showed a significant difference in the performance of maximum repetitions between sets. Conclusion: The time used in the intervals between sets of maximum repetitions doesn’t influence directly the performance of resistance training.